2007
DOI: 10.1074/jbc.m606080200
|View full text |Cite
|
Sign up to set email alerts
|

Gα12 Specifically Regulates COX-2 Induction by Sphingosine 1-Phosphate

Abstract: Sphingosine 1‐phosphate (S1P), a sphingolipid released from activated platelets, stimulates COX‐2 induction. S1P activates GPCRs coupled to Gα family members. This study investigated whether Gα12 family regulates COX‐2 induction by S1P and if so, what the molecular basis is for its COX‐2 regulation. Gene knockout or chemical inhibitor experiments revealed that S1P induction of COX‐2 requires Gα12, but not Gα13, Gαq or Gαi/o. The specific role of Gα12 in COX‐2 induction by S1P was verified by promoter luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…10 However, in mouse embryonic fibroblast cells, S1P-induced COX-2 expression was specifically regulated by Gα 12 . 9 These findings indicated that S1P-induced COX-2 expression might be cell type-specific.…”
Section: Discussionmentioning
confidence: 89%
“…10 However, in mouse embryonic fibroblast cells, S1P-induced COX-2 expression was specifically regulated by Gα 12 . 9 These findings indicated that S1P-induced COX-2 expression might be cell type-specific.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, G␣ 12 -mediated activation of JNK was reported to induce proteasomal degradation of IB␣, leading to the activation of NF-B in the regulation of cyclooxygenase transcription. However, this study did not examine apoptosis (64). Here, we reveal novel suppression of NF-B activity by G␣ 12 through the targeted up-regulation of IB␣ expression.…”
Section: Discussionmentioning
confidence: 99%
“…Davaille et al (17) have reported that S1P treatment causes strong induction of COX-2, which peaks after 3 h and remains elevated for at least 8 h. In contrast, COX-1 expression is not affected by S1P. Subsequently, Ki et al (18) have reported that Ga 12 specifically regulates nuclear factorkB-mediated COX-2 induction by S1P downstream of S1P 1 , S1P 3 , and S1P 5 , in a process mediated by the c-jun N-terminal kinase-dependent ubiquitination and degradation of IkBa. Although they showed that S1P-induced COX-2 induction was not attenuated by RNA interference of S1P 2 , another group has shown that S1P 2 activation induces COX-2 expression (19).…”
Section: Regulation Of Cox-2 Expression By S1pmentioning
confidence: 99%